TEACHING UKRAINIAN AS A FOREIGN LANGUAGE IN HIGHER EDUCATIONAL INSTITUTIONS - Гуркина, Тетяна; Кушнір, Лариса (SWorldJournal, 2022)
The article considers the issues of teaching Ukrainian to foreign citizens, reveals the principles and methods of teaching the Ukrainian language, unveils the process of interaction between teacher and students during training, tells about the stages of l